Introdução à gravitação quântica de laços - Sousa, Luigi Teixeira de (Universidade Federal de São Carlos, 2025)
In the present work, the author will introduce Loop Quantum Gravity (LQG) through the quantization of General Relativity (GR) discretized on a 2-complex via the canonical (introducing operators satisfying the classical Poisson algebra) and covariant (via transition amplitudes given by path integrals) approaches resulting on the Spin Netowork and Spin Foam formalisms respectively, showing the discreteness of the spectra of area and volume and using those results to derive the Bekenstein-Hawking entropy and analyse Big Bang cosmology.
Introduction to loop quantum gravity
Keywords: Gravitação quântica; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::METODOS MATEMATICOS DA FISICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::RELATIVIDADE E GRAVITACAO